Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (Colloque 103 – L’offre des services de santé dans les langues minoritaires, 92e Congrès de l’Acfas, 2025)

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (Colloque 103 – L’offre des services de santé dans les langues minoritaires, dans le cadre du 92e Congrès de l’Acfas, 2025)

Apprentissage de l’offre active des services sociaux et de santé en français par module de simulation interprofessionnelle au bénéfice des francophones en situation minoritaire au Canada - Giroux, Isabelle; Savard, Jacinthe; Tyerman, Jane; Savard, Sébastien; Benoît, Josée; Kengneson, Cris-Carelle (Revista de Llengua i Dret, 2025)
Résumé La formation des futurs prestataires de soins à l’offre active (OA) des services sociaux et de santé (SSS) en français est essentielle pour permettre l’accès équitable à des services de qualité pour les francophones en situation minoritaire (FSM) au Canada. L’apprentissage par module de simulation interprofessionnelle est une avenue prometteuse à évaluer. L’objectif du présent travail est d’évaluer la satisfaction et l’efficacité perçue de l’apprentissage de l’OA des SSS en français à l’aide d’un module de simulation interprofessionnelle spécifique, le MODULE-IP-SIM-OA. En ce qui concerne la méthodologie, des stagiaires de programmes en SSS de l’Université d’Ottawa ont complété le dit module, suivi d’un débreffage synchrone et d’un questionnaire de rétroaction en ligne, entre mai et décembre 2023. Les 216 stagiaires issus de neuf disciplines ont rapporté des taux élevés de satisfaction et d’efficacité perçue concernant le MODULE-IP-SIM-OA et son débreffage. Cet apprentissage, jugé efficace par les stagiaires, pourrait avoir des retombées positives sur l’offre de services aux FSM afin d’atténuer les barrières linguistiques en santé. Resum La formació dels futurs professionals de la salut sobre l’oferta activa (OA) dels serveis socials i de salut (SSS) en francès és essencial per permetre un accés equitatiu a serveis de qualitat a les persones francòfones en situació minoritària (FSM) al Canadà. L’aprenentatge mitjançant un mòdul de simulació interprofessional és una via prometedora que cal explorar. L’objectiu d’aquest treball és avaluar el nivell de satisfacció i d’eficàcia percebuda de l’aprenentatge de l’OA dels SSS en francès amb l’ajuda d’un mòdul de simulació interprofessional específic, el MODULE-IP-SIM-OA. Pel que fa a la metodologia, diversos estudiants en pràctiques de programes de SSS de la Universitat d’Ottawa van completar aquest mòdul, seguit d’una sessió de debrífing síncrona i d’un qüestionari de valoració en línia, entre els mesos de maig i desembre de 2023. Els 216 estudiants, provinents de nou disciplines diferents, van aportar respostes que indiquen nivells alts de satisfacció i d’eficàcia percebuda en relació amb el MODULE-IP-SIM-OA i el debrífing posterior. Aquest aprenentatge, que els participants van considerar eficaç, podria tenir efectes positius en l’oferta de serveis als FSM per reduir les barreres lingüístiques en l’àmbit de la salut. Abstract Training future care providers in the active offer (AO) of social and health services (SHS) in French is essential for ensuring equitable access to quality services for Francophones in minority contexts (FMS) in Canada. Learning through an interprofessional simulation module is a promising approach that warrants evaluation. The purpose of this paper is to assess the satisfaction and perceived effectiveness of learning the AO of SHS in French using a specific interprofessional simulation module, the MODULE-IP-SIM-OA. Regarding methodology, between May and December 2023, trainees from SHS programs at the University of Ottawa completed this module, followed by a synchronous debriefing and an online feedback questionnaire. The 216 trainees from nine disciplines reported high levels of satisfaction and perceived effectiveness regarding the MODULE-IP-SIM-OA and its debriefing. This learning experience, considered effective by the trainees, could have positive impacts on service delivery to FMS and help reduce language barriers in healthcare. Resumen La formación de los futuros profesionales de la salud sobre la oferta activa (OA) de los servicios sociales y de salud (SSS) en francés es esencial para permitir un acceso equitativo a servicios de calidad a las personas francófonas en situación minoritaria (FSM) en Canadá. El aprendizaje mediante un módulo de simulación interprofesional es una vía prometedora que hay que explorar. El objetivo de este trabajo es evaluar el nivel de satisfacción y de eficacia percibida del aprendizaje de la OA de los SSS en francés con la ayuda de un módulo de simulación interprofesional específico, el MODULE-IP-SIM-OA. Con respecto a la metodología, varios estudiantes en prácticas de programas de SSS de la Universidad de Ottawa completaron este módulo, seguido de una sesión de debriefing síncrona y de un cuestionario de valoración en línea, entre los meses de mayo y diciembre de 2023. Los 216 estudiantes, provenientes de nueve disciplinas diferentes, aportaron respuestas que indican niveles altos de satisfacción y de eficacia percibida en relación con el MODULE-IP-SIM-OA y el debriefing posterior. Este aprendizaje, que los participantes consideraron eficaz, podría tener efectos positivos en la oferta de servicios a los FSM para reducir las barreras lingüísticas en el ámbito de la salud.

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

État des lieux pour le secteur des soins à domicile et en milieu communautiare dans le nord de l'Ontario - Réseau du mieux-être francophone du Nord de l'Ontario (2025)
Le Réseau a entrepris le travail de recenser les capacités actuelles du secteur des soins à domicile et en milieu communautaire dans le Nord de l’Ontario, et ce, afin de mieux appuyer les organismes de soins de santé et ainsi renforcer les capacités du secteur. En effet, cette étude permettra au Réseau de connaître les capacités actuelles en termes de professionnels de la santé qui parlent le français dans le Nord de l’Ontario, puis d’identifier les domaines et les régions où les disparités sont plus importantes. Ce rapport pourra servir de guide envers l’établissement des priorités et de stratégies régionales en matière de services en français pour le secteur des soins à domicile et en milieu communautaire.

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)